A Roadmap for the Molecular Farming of Viral Glycoprotein Vaccines: Engineering Glycosylation and Glycosylation-Directed Folding - Margolin, Emmanuel; Crispin, Max; Meyers, Ann; Chapman, Ros; Rybicki, Edward P. (Frontiers in Plant Science, 2020)
Immunization with glycoprotein vaccines is a promising approach to induce immunity against viruses. However, the complex maturation requirements of these glycoproteins typically necessitate their production in mammalian cells to support their folding and post-translational modifications. However, the costs and infrastructure requirements with this approach can be prohibitive in developing countries, and the production scales and timelines may prove limiting when applying these systems to the control of pandemic outbreaks. Molecular farming has been suggested as a cheap and rapidly scalable alternative production system, with the potential to perform post-translational modifications that are comparable to mammalian cells. Consequently, plant-produced glycoprotein vaccines for influenza have shown promise in clinical trials, and vaccines against the newly emergent severe acute respiratory syndrome coronavirus-2 have entered into late stage preclinical and clinical testing. However, many other viral glycoproteins accumulate poorly in plants, and are not appropriately processed due to differences in the host cellular machinery. Furthermore, plant-derived glycoproteins often contain glycoforms that are distinct from those present on the native virus, and may be under-glycosylated in some instances. Recent advances have increased the complexity and yields of biologics that can be produced in plants, and now enable the expression of many viral glycoproteins which could not previously be produced. In contrast to the empirical optimization that predominated during the early years of molecular farming, the next generation of plant-made products are being produced by developing tailor-made approaches to support their production. This has involved the elimination of plant-specific glycoforms and the introduction into plants of elements of the biosynthetic machinery from different expression hosts. These approaches have resulted in the production of mammalian N-linked glycans and the formation of O-glycans in planta. More recently, molecular engineering has also been applied to improve the glycan occupancy of proteins which are not appropriately glycosylated, and to support the folding and processing of viral glycoproteins where the cellular machinery differs from the usual expression host of the protein. Here we highlight recent achievements and remaining challenges in glycoengineering and the engineering of glycosylation-directed folding in plants, and discuss how these can be applied to produce viral glycoproteins vaccines.